2015
DOI: 10.5367/ihe.2015.0254a
|View full text |Cite
|
Sign up to set email alerts
|

Software: University Courses versus Workplace Practice

Abstract: There is a shortage of software developers with the right skills and knowledge, not only in South Africa but worldwide. Despite reports of a gap between industry needs and software education, the gap has mostly been explored in developed countries and in quantitative studies. This paper reports on a mixed methods study of the perceptions of professional software developers regarding what topics they learned from their formal education and the importance of these topics to their actual work. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Most of these studies conducted in the developed countries and used quantitative methods. A mixed method study of the insights of professional software developer shows the topics they learn in their term of education and the significance of these topics in their actual work [12]. The findings of this study suggest that there is a gap between software development education and workplace practices.…”
Section: K Research On Gap Between Software Industry and Se Educationmentioning
confidence: 77%
See 1 more Smart Citation
“…Most of these studies conducted in the developed countries and used quantitative methods. A mixed method study of the insights of professional software developer shows the topics they learn in their term of education and the significance of these topics in their actual work [12]. The findings of this study suggest that there is a gap between software development education and workplace practices.…”
Section: K Research On Gap Between Software Industry and Se Educationmentioning
confidence: 77%
“…The findings of this study suggest that there is a gap between software development education and workplace practices. The study also gives recommendations for the software development education [12].…”
Section: K Research On Gap Between Software Industry and Se Educationmentioning
confidence: 97%
“…We provide more information on this in Section 3.5. The study [21] conducted a survey in South Africa using a taxonomy similar to [15] and [16]. [18] focuses on comparing gaps in technical and soft skills by interviewing 22 participants.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Given Bennett’s (2002) findings, one may be tempted to argue that this could be limited to more people-oriented disciplines like marketing and management. However, the importance of these skills is supported even in data-driven, technically oriented fields such as data science (Fitzgerald et al, 2016), software development (Liebenberg et al, 2015), and accounting (Lee and Blaszczynski, 1999; Von Romburgh and Van Der Merwe, 2015). In fact, even in the context of entry-level data analytics job advertisements, soft skills such as communication, problem-solving, and decision-making were more frequently mentioned than technical proficiency (Cegielski and Jones-Farmer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Voices from both the academy and industry have also been persistent in calling attention to deficiencies in the perceived employability of graduates (Azevedo et al, 2012; Liebenberg et al, 2015). According to a report for the York College of Pennsylvania Center for Professional Excellence (Polk-Lepson Research Group, 2010), business leaders and human resource management professionals found that college graduates lacked the skill sets to meet the demands of the workplace.…”
Section: Literature Reviewmentioning
confidence: 99%